Konsep Balance Scorecard dan Relevansinya dalam Perencanaan Pendidikan Islam - Aida Naja Sabiela; Samsul Susilawati (Al-Kindi, 2026)
This study aims to examine in depth the concepts and basic principles of the balance scorecard relevant to Islamic education management, the stages and perspectives of the balance scorecard that can be applied in Islamic education planning, and the advantages and disadvantages of the balance scorecard in Islamic education strategy planning. It uses a qualitative approach with a library research method. Data was obtained through reviewing various literature such as books, articles, and journals to understand the phenomenon in depth theoretically and conceptually without involving field data collection. The results show that the balance scorecard (BSC) is a strategic management tools that assesses performance through four perspectives: financial, customer, internal processes, learning and growth, so that organizations obtain a more holistic picture of performance. In Islamic education, BSC helps align vision, strategy, programs, and performance indicators, despite its weaknesses such as the need for competent human resources and the potential for to many indicators. However, various studies show that BSC remains effective in improving the quality and performance of institutions in a targeted manner.